Sepsis caused by Salmonella serovar paratyphi B in immunocompromised patient with kasabach-merritt syndrome in dr. Soetoro general academic hospital Surabaya: a case report - Suharyadi Sasmanto; Wasito, Eddy Bagus (Indonesian Society for Clinical Microbiology (Perhimpunan Dokter Spesialis Mikrobiologi Klinik Indonesia), 2023)
Introduction: Salmonella species are recognized worldwide as a common cause of childhood infections, particularly gastroenteritis, bacteremia, and enteric fever. Some salmonella infection cases, especially those caused by Salmonella paratyphi B, which are rare, are reported to cause sepsis in children and neonates. The treatment of Salmonella paratyphi B-induced sepsis is challenging, particularly in immunocompromised babies as in Kasabach-Merritt Syndrome (KMS). This case report aims to report the case of a 1.7-year-old girl who had Salmonella serovar paratyphi B-induced sepsis and presented with KMS. Case description: A 1.7 years old girl has complaints of fever for 5 days prior to admission to the hospital with a history of a growing haemangioma in the abdominal area since the first 40 days since birth. The patient was diagnosed with KMS. During the period of hospitalization, there were no complaints of fever, therefore, the patient was discharged. The next day, the patient complained of persistent fever and general weakness. Vital signs examination revealed tachycardia and hyperthermia. Laboratory results showed the hemoglobin was 8.7 gr/dL, leucocyte 20.640/uL, neutrophil 65%, lymphocyte 20.5%, platelet 14.000 uL, CRP 14.22 mg/dL. The patient was diagnosed with Kasabach-Merritt Syndrome (KMS) and has been in control as an outpatient and received oral therapy with methylprednisolone, propranolol and tranexamic acid. The patient was readmitted for chemotherapy with bleomycin and vincristine as part of the KMS treatment regimen. Empiric antibiotic (200 mg ampicillin i.v.) also administered as Salmonella sp. Bacteria was found on the blood culture. Conclusion: Salmonella paratyphi B is a rare infection, the symptoms are typically mild. Rapid identification of bacterial infection and antimicrobial susceptibility testing is crucial for effective treatment.